Specific Recognition of Breast Cancer Cells In Vitro Using Near Infrared-Emitting Long-Persistence Luminescent Zn3Ga2Ge2O10:Cr3+ Nanoprobes - Li, Jinlei; Shi, Junpeng; Shen, Jiangshan; Man, Huizi; Wang, Mingxi; Zhang, Hongwu (Nano-Micro Letters, 2014)
In this paper, near-infrared emitting long-persistence luminescent Zn3Ga2Ge2O10:Cr3+ (ZGG) nanoparticles with diameters of 30–100 nm and bright luminescence were prepared by a sol–gel synthesis method. After the surface amination, the nanoparticles were further bioconjugated with breast cancer-specific monoclonal antibody (anti-EpCAM) to form ZGG-EpCAM nanoprobes which can specifically target breast cancer cell lines (MCF7) in vitro. The results of in vitro images show that the luminescence signals from the cells treated with ZGG-EpCAM nanoprobes are stronger than those from cells treated with ZGG-unconjugated antibody, indicating that the prepared ZGG-EpCAM nanoprobes possessed excellent specific recognition capability. Furthermore, due to their long afterglow properties, the imaging could persist more than 1 h. Therefore, these nanoprobes could not only provide a high specificity detection method for cancer cells but also realize the long-time monitoring. Developed near-infrared emitting long-persistence luminescent nanoprobes will be expected to find new perspectives for cell therapy research and diagnosis applications.